2023
DOI: 10.1021/acsaem.3c02104
|View full text |Cite
|
Sign up to set email alerts
|

Anion-Exchange Membrane–Photoelectrochemical Water Splitting Using Porous Hematite Photoanodes

Dewangga Oky Bagus Apriandanu,
Rizki Marcony Surya,
Kosuke Beppu
et al.

Abstract: The requirement for liquid electrolytes to maintain their ionic conductivity hinders the practical implementation of photoelectrochemical (PEC) systems. Here, a membrane electrode assembly was fabricated by incorporating porous α-Fe 2 O 3 (hematite)-based photoanodes with an anion-exchange membrane (AEM). AEM−PEC water splitting was demonstrated in pure water without supporting electrolytes over porous hematite photoanodes under visible-light irradiation. This PEC system was operational even under low conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The investigators reported that the average particle size was approximately 11 nm and crystalline in nature (Da'na et al, 2018). Apriandanua et al also showed similar experimental results for pure and composite forms of ferrous in several investigations (Apriandanu et al, 2023b;2023c). (Pallela et al, 2019).…”
Section: Phase Identification Of Ionps By Xrdmentioning
confidence: 69%
“…The investigators reported that the average particle size was approximately 11 nm and crystalline in nature (Da'na et al, 2018). Apriandanua et al also showed similar experimental results for pure and composite forms of ferrous in several investigations (Apriandanu et al, 2023b;2023c). (Pallela et al, 2019).…”
Section: Phase Identification Of Ionps By Xrdmentioning
confidence: 69%
“…Ti 4+ doping increased the donor density of the Fe 2 O 3 layer via the second annealing step in the absence of oxygen [8] . Ti‐doped Fe 2 O 3 /Ti‐felt was further modified by an Al 2 O 3 passivation layer and a cobalt phosphate (CoPi) OER co‐catalyst; porous Ti‐doped Fe 2 O 3 ‐Al 2 O 3 ‐CoPi exhibited a J photo of 0.85 mA cm −2 at 1.23 V vs. RHE in 1 M NaOH (pH 13.6) under 1‐sun illumination (AM1.5G) [31] . The relatively lower performance would be improved by adopting reported preparation methods for the highly efficient hematite photoanodes.…”
Section: Macroporous Photoelectrodesmentioning
confidence: 99%
“…Hence, another type of polymer electrolyte membrane that is suitable for use in alkaline environments is required. Recently, AEMs with hydroxide ion (OH − ) conductivities have been used with porous Fe 2 O 3 ‐based photoanodes [31] . A Ti‐doped Fe 2 O 3 layer was prepared on a titanium felt substrate and subsequently modified with an Al 2 O 3 passivation layer and a CoPi co‐catalyst.…”
Section: Polymer Electrolyte Photoelectrochemistrymentioning
confidence: 99%